2018
DOI: 10.1590/0102-311x00188016
|View full text |Cite
|
Sign up to set email alerts
|

Internações por complicações obstétricas na gestação e desfechos maternos e perinatais, em uma coorte de gestantes no Sistema Único de Saúde no Município de São Paulo, Brasil

Abstract: A morbidade materna, a mortalidade neonatal e a mortalidade fetal são importantes indicadores da saúde materna infantil. O estudo tem por objetivo descrever desfechos maternos e perinatais (baixo peso ao nascer, prematuridade, óbito fetal e neonatal, internações pós-parto e readmissão dos recém-nascidos) de uma coorte de gestantes cujos partos foram financiados pelo Sistema Único de Saúde (SUS) no Município de São Paulo, Brasil, no segundo semestre de 2012. Foi obtida uma coorte retrospectiva de 55.404 gestant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
40

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 26 publications
0
7
0
40
Order By: Relevance
“…In Brazilian pregnant women, the more common complications are hypertensive disorders and infections (urinary tract infection and vaginosis) [22]. The related nutritional condition has an association between overweight/obesity and micronutrient deficiency, especially for iron and vitamins A and D [23, 24].…”
Section: Discussionmentioning
confidence: 99%
“…In Brazilian pregnant women, the more common complications are hypertensive disorders and infections (urinary tract infection and vaginosis) [22]. The related nutritional condition has an association between overweight/obesity and micronutrient deficiency, especially for iron and vitamins A and D [23, 24].…”
Section: Discussionmentioning
confidence: 99%
“…That study concluded that these events should be considered to be sentinel events for monitoring childbirth and newborn health care in the population served by the Brazilian National Health System (SUS). 20 For the epidemiological surveillance of deaths service, the experience described by this report reaffirmed work processes based on building and sharing information and recommending procedures, thus contributing to the practices of Primary Health Care professionals being articulated with health surveillance actions. In 2013, the year in which the Target 35 Project started, the third and last maternal death recorded in Porto Seguro occurred in June.…”
Section: Gestational Risk Classificationmentioning
confidence: 67%
“…Estas altas taxas de mortalidade feminina ocorreram devido aos indicadores de saúde atrelados à gestação de alto risco. Em 2015, foi estimada a ocorrência de 303 mil óbitos maternos, 2,6 milhões de óbitos fetais e 2,7 milhões de óbitos neonatais no mundo (MOURA et al, 2018). Eu tenho muito medo dos profissionais, da equipe.…”
Section: Acompanhamento Na Gestação De Alto Risco Centrado No Modelo unclassified